Improving the quality of healthy schools through the management of the school healthy kitchen - Dwi Lindarto; Harisdani, Devin Defriza; Suwantoro, Hajar; Abdillah, Wahyu; Irsal (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2020)
In the kindergarten education program (Taman Kanak-kanak; TK), Medan Zahira School as a healthy school partner, runs an activity based on the formation of healthy behavior and culture in terms of good eating habits. In its implementation, this education is carried out every day with lunch together in class by all students and is something that requires good, orderly, efficient and healthy food management. Low understanding of room design arrangements and healthy kitchen utensils as well as a lack of manuals for improving healthy kitchen facilities for kindergartens and the limited space available for school kitchen facilities that require creativity in arranging a healthy school kitchen arrangement. In addition, it is necessary to develop creativity for teachers in arranging school kitchen facilities which is a partner problem. Through the 2020 TALENTA USU Community Service Program, training on healthy kitchen design and capacity building for teachers on knowledge and skills in healthy kitchens is additional knowledge for educators / teachers in understanding, compiling manuals, designing healthy kitchen models through This activity begins with the introduction and understanding of work activities in the kitchen for kindergarten students' lunch preparations as the basis for preparing a healthy school kitchen layout plan.